Resident memory T cells, critical components in tumor immunology. Issue 1 (4th September 2018) - Mami-Chouaib, Fathia; Blanc, Charlotte; Corgnac, Stéphanie; Hans, Sophie; Malenica, Ines; Granier, Clémence; Tihy, Isabelle; Tartour, Eric
Abstract : CD8 + T lymphocytes are the major anti-tumor effector cells. Most cancer immunotherapeutic approaches seek to amplify cytotoxic T lymphocytes (CTL) specific to malignant cells. A recently identified subpopulation of memory CD8 + T cells, named tissue-resident memory T (TRM ) cells, persists in peripheral tissues and does not recirculate. This T-cell subset is considered an independent memory T-cell lineage with a specific profile of transcription factors, including Runx3 +, Notch +, Hobit +, Blimp1 +, BATF +, AHR +, EOMES neg and Tbet low . It is defined by expression of CD103 (αE (CD103)β7 ) and CD49a (VLA-1 or α1 β1 ) integrins and C-type lectin CD69, which are most likely involved in retention of TRM cells in non-lymphoid tissues, including solid tumors. CD103 binds to the epithelial cell marker E-cadherin, thereby favoring the location and retention of TRM in epithelial tumor regions in close contact with malignant cells. The CD103-E-cadherin interaction is required for polarized exocytosis of lytic granules, in particular, when ICAM-1 expression on cancer cells is missing, leading to target cell death. TRM cells also express high levels of granzyme B, IFNγ and TNFα, supporting their cytotoxic features. Moreover, the local route of immunization targeting tissue dendritic cells (DC), and the presence of environmental factors (i.e. TGF-β, IL-33 and IL-15), promote differentiation of this T-cell subtype. In both spontaneous tumor models and engrafted tumors, natural TRM cells or cancer-vaccine-induced TRM directly control tumor growth. In line with these results, TRM infiltration into various human cancers, including lung cancer, are correlated with better clinical outcome in both univariate and multivariate analyses independently of CD8 + T cells. TRM cells also predominantly express checkpoint receptors such as PD-1, CTLA-4 and Tim-3. Blockade of PD-1 with neutralizing antibodies on TRM cells isolated from human lung cancer promotes cytolytic activity toward autologous tumor cells . Thus, TRM cells appear to represent important components in tumor immune surveillance. Their induction by cancer vaccines or other immunotherapeutic approaches may be critical for the success of these treatments. Several arguments, such as their close contact with tumor cells, dominant expression of checkpoint receptors and their recognition of cancer cells, strongly suggest that they may be involved in the success of immune checkpoint inhibitors in various cancers.